2014
DOI: 10.1038/ejcn.2013.271
|View full text |Cite
|
Sign up to set email alerts
|

Sources of vegetables, fruits and vitamins A, C and E among five ethnic groups: Results from a multiethnic cohort study

Abstract: Objectives Data are limited on how dietary sources of food and nutrients differ among ethnic groups. The objective of this study was to determine the main sources of fruit, vegetables, and vitamins A, C, and E for five ethnic groups. Methods Dietary data were collected using a validated quantitative food frequency questionnaire from participants in the Multiethnic Cohort in Hawaii and Los Angeles County between 1993 and 1996. Data were analyzed for 186,916 participants representing five ethnic groups; Africa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 28 publications
1
38
1
1
Order By: Relevance
“…Fruit and vegetable intake might serve as another example. There are large cultural differences and possibly differences in nutrient composition in such foods consumed (36). Sharma et al (36) observed great ethnic variation in food sources of vitamins A, C, and E, which implies that the biological impact of diet on disease may differ on the basis of the foods that ethnic groups consume.…”
Section: Discussionmentioning
confidence: 98%
“…Fruit and vegetable intake might serve as another example. There are large cultural differences and possibly differences in nutrient composition in such foods consumed (36). Sharma et al (36) observed great ethnic variation in food sources of vitamins A, C, and E, which implies that the biological impact of diet on disease may differ on the basis of the foods that ethnic groups consume.…”
Section: Discussionmentioning
confidence: 98%
“…), member of Cactaceae family, is characterized by a thick pericarp with small prickles, colors from yellow to purple, and juicy pulp full of seeds (Sáenz 2000;Zito et al 2013). From the nutrimental view point, prickly pear fruit contains ascorbic acid (0.02 -0.04%), fibre (0.02-3.15%) and some essential amino acids like methionine and phenylalanine (El Gharras 2011;Herrera-Hernández et al 2010;Ozcan & Juhaimi 2011;Piga et al 2003;Sharma et al 2014). The caloric value of its pulp is 209.34 kJ/100 g, comparable to other fruits such as pear, apricot and orange (Felker et al 2002;Herrera-Hernández 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Our study and the former study used different methods. The current study used food frequency questionnaires which have been adopted by many recent studies in evaluating attitude, frequency, knowledge and efficacy related to fruit and vegetable intake by school children (Sharma et al, 2014, Emily M, 2016, Neumark-Sztainer et al,, 2012. The previous study used students' nutritional behaviors regarding fruit and vegetables evaluated through 24-hour recall journals.…”
Section: Discussionmentioning
confidence: 99%
“…The previously validated tool for self-efficacy related to fruits and vegetable consumption for adolescents aged 11-19 by Hagler et al, 2005, Bandura, 2006, andSharma et al, 2014 was adopted after it was optimized to meet the local fruits and vegetables. This was called the fruit and vegetable efficacy questionnaire (FVEQ).…”
Section: Design Of Instruments For Data Collectionmentioning
confidence: 99%